A NEW CLASSIFICATION OF THE RADIOLARIA - Afanasieva M.S.; Amon E.O. (My University, 2003)
A new classification of higher radiolarian taxa is proposed. The phylum Radiolaria includes two superclasses, i.e., Pheodaria and Polycystina. The superclass Polycystina is composed of the following five classes: Sphaerellaria Haeckel, 1881; Spumellaria Ehrenberg, 1875; Stauraxonaria Afanasieva, 2000; Aculearia Afanasieva, 1999, status nov.; and Nassellaria Ehrenberg, 1847. The class Aculearia combines three orders, i.e., Fasciculata ordo nov., Triangulata ordo nov., and Albaillellata Deflandre, 1953, emend. Afanasieva, 1999. The class Spumellaria consists of four orders, i.e., Collodariata Haeckel, 1881; Echidninata Kozur, Mostler et Repetski, 1996; Cancelliata ordo nov., and Spongiata ordo nov. A special attention was paid to the systems and evolution of spinaceous and spongy Paleozoic radiolarians.
Keywords: New classification; Radiolaria; higher taxa; evolution